Workload and academic procrastination among working students - Raudia, Al Fatha (Faculty of Psychology, Universitas Negeri Yogyakarta, 2023)
The phenomenon of working students playing two roles is common occurence these days. Because of their dual roles, they may have a workload that affects the emergence of academic procrastination in working students. The purpose of this study was to examine how workload affected academic procrastination in working students. This is a quantitative study using a technique of purposive sampling. The workload and academic procrastination scales were applied in this study. We conducted a survey of 118 working students. Based on a simple linear regression test on workload and academic procrastination variables, we concluded that there was no significant effect of workload on academic procrastination of working students, F (1,116) = 4.75, p. 05, R2 =.039, R2 adjusted =.031. The regression coefficient (B = -.104) indicates that a 1-point increase in workload will result in a 0.104-point decrease in academic procrastination.